The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/bf02550283
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of premature ejaculation with sertralin

Abstract: To evaluate the efficacy of oral sertralin in the treatment of premature ejaculation, out of 22 patients with premature ejaculation 16 received oral sertralin, 50 mg a day for at least 2 weeks. Four patients were lost to follow-up. Two patients interrupted treatment due to side effects of sertralin. Out of 16 patients who completed at least a two-week period of treatment 14 (87.5%) responded clinically. Clinical response was achieved in the first week of treatment in 11 of 16 responders (68.75%). We conclude t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
8
0
1
Order By: Relevance
“…[24][25][26] Sertraline at daily doses of 25-50 mg has been repeatedly reported to improve not only the ejaculation latency time in men with PE but also the control over ejaculation and sexual satisfaction, as evidenced by open-label and controlled studies that reported subsequent increased frequency of intercourse. [27][28][29] Similar to other types of SSRIs, sertraline reaches Cmax within 4-6 h following administration. On the basis of these findings, the current study used EEG to examine the effects of 50 mg sertraline on cerebral activation 4 h after its administration.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…[24][25][26] Sertraline at daily doses of 25-50 mg has been repeatedly reported to improve not only the ejaculation latency time in men with PE but also the control over ejaculation and sexual satisfaction, as evidenced by open-label and controlled studies that reported subsequent increased frequency of intercourse. [27][28][29] Similar to other types of SSRIs, sertraline reaches Cmax within 4-6 h following administration. On the basis of these findings, the current study used EEG to examine the effects of 50 mg sertraline on cerebral activation 4 h after its administration.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, higher-frequency oscillatory cortical activity, in the range of 40-60 Hz, is seen in less widely dispersed cell assemblies. 8 The highest frequency band can be analyzed by LORETA as a high-frequency beta band (22)(23)(24)(25)(26)(27)(28)(29)(30). The analysis of this frequency band can be helpful when evaluating neurocognitive functions during various situations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further studies (prospective studies and randomized controlled trials) have confirmed the efficacy of sertraline in the management of PE [Balbay et al 1998;Biri et al 1998;Mendels, 1995]. Duloxetine [Athanasios et al 2007] and Escitalopram [Safarinejad, 2007] have also been shown to be effective in treating PE.…”
Section: Tricyclic Antidepressants (Clomipramine)mentioning
confidence: 99%
“…From clinical studies, such drugs have certain effects in curing premature ejaculation, but with extremely obvious side effects. In this research, 5 patients exhibited side effects of different levels, including lethargy, dysphoria, bruxism and nausea, which disappeared 2 to 3 days later after drug withdrawal [3][4][5]. For patients suffering renal failure, there is still no report about whether these drugs can be used.…”
Section: Discussionmentioning
confidence: 82%